Correlation Between Learning Motivation and Learning Outcomes of English as a Foreign Language: Case Study of English Students at Universitas Muhammadiyah Makassar - Awalia, Rezki (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This study comprehensively analyzes the relationship between learning motivation and English language learning outcomes among EFL students. Utilizing a quantitative approach, the research examines the distinct motivational profiles of students, identifies prevalent patterns and trends, and offers practical insights for educators and curriculum developers in higher education. The study identifies intrinsic and extrinsic motivations as two key factors influencing students' academic performance in English language studies. Notably, the findings indicate that extrinsic motivation, encompassing external incentives such as rewards or recognition, demonstrates a stronger correlation with students' academic achievements compared to intrinsic motivation. The research underscores the significance of understanding and leveraging these motivational factors to enhance English language teaching strategies and student learning experiences. By integrating awareness of both intrinsic and extrinsic motivations into educational practices, educators, and policymakers can foster a supportive learning environment conducive to improved student success and proficiency in English language acquisition. This study contributes valuable insights for enhancing pedagogical approaches to optimize academic outcomes in English language education.